Erstattung der Tabakentwöhnung: Gesetzgeber muss Blockade aufheben - Hering, Thomas; Batra, Anil; Mühlig, Stephan (DMW - Deutsche Medizinische Wochenschrift, 2020)
A constitutional expert opinion, which reviews the social and constitutional foundations of tobacco cessation within the framework of statutory health insurance in Germany, comes to the conclusion that the legislator must release the reimbursement of professional tobacco cessation as a curative service by the statutory health insurance – and not only as a subsidy for a psychotherapeutically oriented measure within the framework of prevention.
Keywords: Tabakabhängigkeit; Raucherentwöhnung; Kostenerstattung; Gesundheitsgesetzgebung